STRATEGY OF FINANCIAL MANAGEMENT OF MSMEs IN THE DIGITAL 5.0 ERA OF PALU BUSINESS INCUBATOR - Christina Agnelya Bosara; Juliana Kadang; Darman Darman; Cici Rianty K. Bidin (Journal of Management Small and Medium Enterprises (SME's))
This study aims to analyze the financial management strategies of MSMEs in the digital 5.0 era, focusing on four main indicators, namely budget planning and use, financial recording, financial reporting, and financial control. The research was conducted on 31 MSMEs registered at the Palu City Business Incubator, using descriptive quantitative methods. Data were collected through a questionnaire with a Likert scale and analyzed using descriptive statistics through frequency tabulation. The results showed that the majority of MSMEs have implemented financial management strategies well in the aspects of financial planning, recording, and control. The utilization of digital technology is proven to support the effectiveness of financial management, especially in preparing budgets, recording transactions, and monitoring cash flow in real-time. However, in the aspect of financial reporting, there are still shortcomings, where most MSMEs have not prepared complete financial reports such as balance sheets, income statements, and cash flows. Nevertheless, some MSMEs have used digital technology to prepare financial reports more quickly and accurately. Overall, this study indicates that the financial management of MSMEs in the digital 5.0 era is quite good but still requires strengthening in the aspect of financial reporting to support business sustainability.